2022
DOI: 10.1111/asj.13679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oligosaccharides on serum biochemical index, intestinal morphology, and antioxidant status in broilers

Abstract: In order to determine the effect of different oligosaccharides on growth performance, intestinal health, and antioxidant status of broilers, 240 1-day-old XiangHuang broilers were randomly distributed to 4 treatments with 6 replicates each. Birds were fed corn-soybean-based diets (CON), and birds in xylooligosaccharides (XOS), fructo-oligosaccharides (FOS), and iso-maltooligosaccharide (IMO) groups were given the basal diet supplemented with 200 mg/kg XOS, FOS, and IMO, respectively. Result showed that average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…34 Currently, oligosaccharides such as chitosan, mannan oligosaccharides, and fructooligosaccharides have been applied to human health and animal breeding as intestinal protective agents. 35 As the main component of Poria cocos, PCPs have a beneficial effect on human health. [36][37][38] In previous studies, PCPs had been degraded into PCOs, and it was proved that PCOs could act as a prebiotic to treat glucolipid disorders by reshaping the structure of intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…34 Currently, oligosaccharides such as chitosan, mannan oligosaccharides, and fructooligosaccharides have been applied to human health and animal breeding as intestinal protective agents. 35 As the main component of Poria cocos, PCPs have a beneficial effect on human health. [36][37][38] In previous studies, PCPs had been degraded into PCOs, and it was proved that PCOs could act as a prebiotic to treat glucolipid disorders by reshaping the structure of intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…T-AOC is a comprehensive index used to measure the antioxidant capacity of the body [ 28 ]. As the final product of lipid peroxidation, MDA content can directly reflect the degree of cell membrane oxidation [ 29 ]. The results showed that the oregano oil combined with macleaya cordata oral solution could significantly improve the total antioxidant capacity of broilers, significantly increase the activities of superoxide dismutase and glutathione peroxidase in the serum of broilers and reduce the content of malondialdehyde in the serum of broilers to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…However, we added it to drinking water in the form of oral liquid, and some studies showed that the effect of adding it to drinking water was better than that of adding it to feed. Adding drugs into drinking water was more beneficial to the absorption of broilers and reduced the dosage of drugs, thus playing a greater role [ 29 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum biochemical indices can give an index to the metabolism and health condition of the organism, as well as the responses of body to external and internal stressors and stimuli ( Yang et al, 2022 ). Albumin is a small molecule protein, which is an important protein of the body and is produced by the liver mostly.…”
Section: Discussionmentioning
confidence: 99%